Reciprocal effects of esport participation and mental fatigue among Chinese undergraduate students using dynamic structural equation modeling. (September 2022) - Luo, Yan; Hutchinson, Jasmin C.; O'Connell, Colleen S.; Sha, Yanru
Abstract: Esport has emerged as a global phenomenon in recent years, particularly among college students, but limited studies have examined its relationship with mental fatigue. This study aimed to examine the relationship between esport participation and mental fatigue among Chinese undergraduate students. Data from 63 college students who completed a 15-day survey were analyzed using bivariate dynamic structural equation modeling. Results showed that 80.95% of students who played more esport also experienced more mental fatigue immediately after gameplay. In addition, 25.40% of students who experienced increased mental fatigue immediately after gameplay reduced their subsequent esport participation time 12 h later. In general, students who participated in esport for longer were more likely to experience higher mental fatigue, lingering feelings of mental fatigue, and to reduce their subsequent esport participation time as a result of previously increased after-game mental fatigue. Our findings suggest that participating in more esport not only leads to increased mental fatigue immediately following gameplay, but that a sustained high level of esport participation is also associated with a consistent high level of mental fatigue and a lingering feeling of mental fatigue. Health promotion professionals and policymakers should explore measures that might be implemented to promote healthier esport behaviors among college students. Highlights: Esport participation positively predicted after-game mental fatigue for a majority of college students. After-game mental fatigue negatively predicted later esport participation for a minority of college students. Persistent high level of esport participation is connected with a consistent high level of mental fatigue. Persistent high level of esport participation is connected with a lingering feeling of mental fatigue.